2007
DOI: 10.1016/j.neuron.2006.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Trigeminal Ganglion Neurons during Natural Whisking Behaviors in the Awake Rat

Abstract: Rats use their whiskers to locate and discriminate tactile features of their environment. Mechanoreceptors surrounding each whisker encode and transmit sensory information from the environment to the brain via afferents whose cell bodies lie in the trigeminal ganglion (Vg). These afferents are classified as rapidly (RA) or slowly (SA) adapting by their response to stimulation. The activity of these cells in the awake behaving rat is yet unknown. Therefore, we developed a method to chronically record Vg neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 72 publications
(94 reference statements)
10
104
0
Order By: Relevance
“…It has been reported that rat free-whisking (i.e., with no contacts) generates a sensory signal [40], [41]. This signal is analogous to the self-generated signal observed in our whisking robot.…”
Section: Possible Neural Substrates Of a Contact Detection Scheme supporting
confidence: 79%
“…It has been reported that rat free-whisking (i.e., with no contacts) generates a sensory signal [40], [41]. This signal is analogous to the self-generated signal observed in our whisking robot.…”
Section: Possible Neural Substrates Of a Contact Detection Scheme supporting
confidence: 79%
“…At the present time, it is not clear from ganglion recordings whether these parameters can be measured independently [16,33]. In contrast, it seems more likely that the rat would be able to measure axial force (F x in figure 1c) independently of the bending moment [34].…”
Section: Methods For Radial Distance Determinationmentioning
confidence: 72%
“…On the other hand, it has been shown that in rats sensory signals are generated by whisking movements. Specifically, a study by Leiser and Moxon reported that trigeminal ganglion cells of the rat fired during active whisking in air with no object contacts but were silent when the whiskers were at rest (Leiser and Moxon, 2007). The implication of this result is that whisker sensory signals may include self-generated artefacts during whisking.…”
Section: The Cerebellum Viewed As An Adaptive Filter and Forward Modelmentioning
confidence: 99%
“…The weights of the adaptive filter in the noise cancellation scheme (figure 6a) are adjusted by removing the correlations in the clean signal from the reference noise, implemented via the LMS rule. In the context of whisking, the self-generated noise is thought to be caused by the movement of the whisker, either by inertia of the whisker base in the follicle or the whisker musculature pressing and activating the mechanoreceptors (Leiser and Moxon, 2007). Ultimately, this activation is caused by the motor command to the whisker plant.…”
Section: The Cerebellum Viewed As An Adaptive Filter and Forward Modelmentioning
confidence: 99%